Estudo das propriedades ópticas e morfológicas de pós de SrMoO4 processados em sistemas hidrotérmicos - Sczancoski, Júlio César (2011)
In the last years, the luminescent emissions of SrMoO4 have been investigated for technological applications in solid-state lasers, light emission diodes, cell phone displays and lamps. In terms of synthesis routes, the hydrothermal systems have received special attention of the scientific community because of the versatility in the formation and crystallization processes of ceramic oxides at low temperature conditions (from 100 °C to 250 °C). Besides the reduced costs and environmentally friendlies, these methods are able to allow a control on the morphologies and particle sizes. Hence, in this research, SrMoO4 powders were synthesized by the co-precipitation reaction and processed in conventional and microwave-hydrothermal systems at 140 °C for 2 h. Thus, it was analyzed the influence of the hydrothermal conditions and the different strontium precursors on the optical and morphological properties of these powders. As experimental results, the X-ray diffraction patterns and the Raman-active vibration modes proved that all powders have a scheelite-type tetragonal structure. Diffraction peaks associated to the secondary phases were only identified in the samples prepared with strontium carbonate. The Rietveld refinements suggested the existence of distortions on both [SrO8] and [MoO4] clusters. The typical bending symmetric and stretching anti-symmetric modes between the O-Mo-O bonds were detected by the infrared spectroscopy. The field-emission gun scanning electron microscopy images revealed that the distinct strontium precursors as well as the hydrothermal conditions were able to change the microcrystal shapes. The adsorption/desorption isotherms showed profiles of type IV with hysteresis curves similar to the H3, suggesting the predominance of slit-like vacant spaces between the particles. The ultravioletvisible absorption spectra indicated the presence of intermediary energy levels within the band gap, which are arising from structural defects in the materials. xvi When excited with 350 nm wavelengths, all samples exhibited broad band photoluminescence emissions. Moreover, the profiles of these spectra were influenced by the precursors and/or hydrothermal treatments.